MRI-Fusion Targeted vs. Systematic Prostate Biopsy–How Does the Biopsy Technique Affect Gleason Grade Concordance and Upgrading After Radical Prostatectomy? - Rührup, Jessica; Preisser, Felix; Theißen, Lena; Wenzel, Mike; Roos, Frederik C.; Becker, Andreas; Kluth, Luis A.; Bodelle, Boris; Köllermann, Jens; Chun, Felix K. H.; Mandel, Philipp (Frontiers in Surgery, 2019)
Introduction MRI-targeted biopsy (TB) increases overall prostate-cancer (PCa) detection-rates and decreases the risk of insignificant PCa detection. However, the impact of these findings on the definite pathology after radical prostatectomy (RP) is under debate. Materials and Methods Between 01/2014 and 12/2018, 366 patients undergoing prostate biopsy and RP were retrospectively analyzed. The correlation between biopsy Gleason-score (highest Gleason-score in a core) and the RP Gleason-score in patients undergoing systematic biopsy (SB-group) (n=221) or TB+SB (TB-group, n=145) was tested using the ISUP Gleason-group grading (GGG, scale 1-5). Sub analyses focused on biopsy GGG 1 and GGG ≥2. Results: Proportions of biopsy GGG 1-5 in the SB-group and TB-group were 24.4%, 37.6%, 19%, 10.9%, 8.1% and 13.8%, 43.4%, 24.2%, 13.8%, 4.8%, respectively (p= 0.07). Biopsy and pathologic GGG were concordant in 108 of 221 (48.9%) in SB- and 74 of 145 (51.1%) in TB-group (p=0.8). Gleason upgrading was recorded in 33.5% and 31.7% in SB- vs. TB-group (p=0.8). Patients with biopsy GGG 1 undergoing RP showed an upgrading in 68.5% (37/54) in SB- and 75% (15/20) in TB-group (p=0.8). In patients with biopsy GGG ≥2 concordance increased for both biopsy approaches (54.5% vs. 55.2% for SB- vs. TB-group, p=0.9) Discussion: Irrespective of differences in PCa detection-rates between TB- and SB-groups, no significant differences in GGG concordance and upgrading between patients of both groups undergoing biopsy, followed by RP, were recorded. Concordance rates increased in men with biopsy GGG ≥2. TB seems to detect more patients with PCa without a difference in concordance with final pathology.